2013
DOI: 10.1093/glycob/cwt065
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of major fucosylated and sialylated human milk oligosaccharides by isolated human gut microbes

Abstract: Human milk oligosaccharides (HMOS) are not digested in the proximal intestine. In distal intestine, HMOS collectively modify the microbiota, but the response of individual bacteria to individual components of the HMOS is not well defined. Here, each of 25 major isolates of the human intestinal microbiota was fed individual major fucosylated and sialylated HMOS in anaerobic culture. This allowed for an assessment of the influence of specific HMOS on the growth and metabolic products of individual microbiota bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
285
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(313 citation statements)
references
References 39 publications
(40 reference statements)
23
285
1
4
Order By: Relevance
“…The ability of 2#-FL to inhibit C. jejuni binding is consistent with the inverse relation between concentrations of 2-linked fucosyl oligosaccharides in milk consumed by infants and the risk of C. jejuni-caused moderate-tosevere diarrhea in a prospective study in breastfeeding motherinfant dyads (16,17). Prebiotic activity of oligosaccharides also may be protective (18,19); these indigestible glycans provide a carbon source for mutualistic bacteria that promote the colonization of the gut by a protective community of microbes.…”
Section: Introductionsupporting
confidence: 61%
“…The ability of 2#-FL to inhibit C. jejuni binding is consistent with the inverse relation between concentrations of 2-linked fucosyl oligosaccharides in milk consumed by infants and the risk of C. jejuni-caused moderate-tosevere diarrhea in a prospective study in breastfeeding motherinfant dyads (16,17). Prebiotic activity of oligosaccharides also may be protective (18,19); these indigestible glycans provide a carbon source for mutualistic bacteria that promote the colonization of the gut by a protective community of microbes.…”
Section: Introductionsupporting
confidence: 61%
“…The Sus system thus appeared to be an efficient and well-coordinated machinery to sequester HMOS by employing the mucusutilisation machinery (Marcobal et al 2011). In the co-culture with Anaerostipes caccae, We found that Bacteroides thetaiotaomicron effectively utilised most of the low molecular weight HMOS as previously reported (Yu et al 2013), with differential preference for specific HMOS structures. The glycan-foraging capability could enhance the bacterial fitness and colonisation in the infant gut (Martens et al 2008) and the finestructure prioritisation at species level has been accounted for the collective fitness of Bacteroides spp.…”
Section: Differential D-and L-lactate Metabolism By Gut Commensalssupporting
confidence: 79%
“…The glycans expressed on the surface of the infant intestinal mucosa have been demonstrated to select for distinct bacteria; specifically, the fucosylated glycans of secretors select for microbes that utilize fucose (31). This is complemented by the prebiotic effect of the dominant fucosylated oligosaccharides of human milk, which are prebiotic, and specifically stimulate the growth of bifidobacteria and bacteriodes, predominant mutualists in healthy microbiota (32,33).…”
Section: Prebiotic Role Of Human Milkmentioning
confidence: 99%
“…Thus, HMOS and their major fucosylated components are prebiotic to the mutualists and the mutualist fermentation products inhibit pathogens and opportunists. Moreover, HMOSs, and especially fucosylated HMOSs could promote the growth of specific pioneering or keystone species of human microbiota, thereby shaping birth and milk inocula into a mutualist symbiotic microbiota (32). This is a potential mechanism whereby human milk could confer long term beneficial effects on infant health well after weaning.…”
Section: Prebiotic Role Of Human Milkmentioning
confidence: 99%